The tempest - Shakespeare, William, 1564-1616 (United Kingdom : Sweet Cherry Publishing Limited, 2015)
The Tempest is a romance, problematically embedded in 17th century debates about authority and power. This text focuses upon contemporary texts, looking at the implications of Prospero's magic, his political and paternal ambitions.
Primary
800-899
Keywords: Shakespeare, William, -- 1564-1616; Political refugees -- Juvenile literature; Shipwreck victims -- Juvenile literature; Magicians -- Juvenile literature; Fathers and daughters -- Juvenile literature; Castaways -- Juvenile literature; Spirits -- Juvenile literature; Islands -- Juvenile literature